Evolution of the electronic structure of a Mott system across its phase diagram: an X-ray absorption spectroscopy study of (V(1-x)Crx)2O3 - Rodolakis, Fanny; Haverkort, Maurits W. (Arxiv, 2011)
V2O3 is an archetypal system for the study of correlation induced, Mott-Hubbard metal-insulator transitions. Despite decades of extensive investigations, the accurate description of its electronic properties remains an open problem in the physics of strongly correlated materials, also because of the lack of detailed experimental data on its electronic structure over the whole phase diagram. We present here a high resolution X-ray absorption spectroscopy study at the V K-edge of (V(1-x)Crx)2O3 to probe its electronic structure as a function of temperature, doping and pressure, providing an accurate picture of the electronic changes over the whole phase diagram. We also discuss the relevance of the parallel evolution of the lattice parameters, determined with X-ray diffraction. This allows us to draw two conclusions of general interest: first, the transition under pressure presents peculiar properties, related to a more continuous evolution of the lattice and electronic structure; second, the lattice mismatch is a good parameter describing the strength of the first order transition, and is consequently related to the tendency of the system towards the coexistence of different phases. Our results show that the evolution of the electronic structure while approaching a phase transition, and not only while crossing it, is also a key element to unveil the underlying physical mechanisms of Mott materials .
Im Titel sind die Ziffern und Buchstaben 1−x, x, 2 und 3 tiefgestellt
Gesehen am 27.11.2017